Penerapan Model Pembelajaran Kelompok Dalam Meningkatkan Motivasi Belajar Siswa Melalui Pendekatan Developmentally Appropriate Practice (DAP) - Rukiah; Malik, Lina Revilla (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to: a) determine whether the application of the group learning model can increase the learning motivation of children aged 5-6 years; b) determine whether the use of the Developmentally Appropriate Practice (DAP) approach enhances the learning motivation of children aged 5-6 years; and c) examine how the application of the group learning model with the Developmentally Appropriate Practice (DAP) approach can improve learning motivation in children aged 5-6 years. This is a field study, and the data analysis technique used is qualitative descriptive. The data in this study were obtained through observation. Based on the research findings for children aged 5-6 years, the group learning model can increase students' learning motivation through the Developmentally Appropriate Practice (DAP) approach, where children are able to collaborate, discuss ideas, share, and take responsibility.